PREDICTION OF THE SHELF LIFE OF COOKIES Chlorella sp USING DIFFERENT PACKAGING - Rajiv Ramandha Putra; Suparmi Suparmi; Dewita Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis study aimed to estimate the shelf life of Chlorella sp cookies in different packaging using HDPE and aluminum foil packaging. The method used was Arrhenius and stored at a temperature of 25ºC and 35ºC with an observation time interval of 5 days for 30 days. Parameters observed were organoleptic fungal growth and moisture content. The results showed that on the 30th day organoleptically, the Chlorella sp cookies had not grown mushrooms, the moisture content of the Chlorella sp cookies packaged with HDPE at 25ºC storage had a shelf life of 101.07 or 3.37 months, and those stored at 35ºC storage temperature was 81.49 days or 2.72 months. In aluminum foil packaging storage at 25ºC had a shelf life of 117.08 days or 3.90 months and at a temperature of 35ºC, which was 150.29 days or 5.01 months. Keywords: Arrhenius, Alumunium foil, Cookies, HDPE, Shelf life